The effect of a futsal match on some mucosal immunity responses in Female Futsal Players - وحید ساری صرّاف; احمد آزاد; جواد وکیلی; زهرا عبدی اغجه کهلی (Shahid Beheshti University, 2017)
Introduction: Competitive sports is a stress factor to change the immune system. The aim of this study was to evaluate the effect of a futsal match on the responses of mucosal immunity in female futsal players. Methodology: Nine futsal players from one teams of the premier league female futsal in Iran with a mean age of 25± 2 years, BMI 21/03 ± 1/30 kg.m-2, VO2max 47/32 ± 1/62 ml.kg-1.min-1 participated in this study. Unstimulated saliva samples were collected before, after, 24 h and 48 h post- match. In order to analyze the data, descriptive statistics and analysis of variance (ANOVA) with repeated measures post hoc test was carryout by Bonferroni used (P